One-pot construction of random, gradient and triblock copolymers from CO2, epoxides and phthalic anhydride by metal-free catalyst. (November 2022) - Ye, Shuxian; Ren, Yansong; Liang, Jiaxin; Wang, Shuanjin; Huang, Sheng; Han, Dongmei; Huang, Zhiheng; Liu, Wei; Xiao, Min; Meng, Yuezhong
Abstract: Random and gradient terpolymers are successfully synthesized by one-pot copolymerization of epoxides/ethylene oxide (EO)/CO2 and phthalic anhydride (PA)/EO/CO2 via triethylborane (TEB)-activated catalysis, respectively. The random terpolymer of cyclohexene oxide (CHO)/EO/CO2 exhibits one glass transition temperature ( T g ), which can be adjusted in the range of 26–126 °C by simply varying CHO content. The PA/EO/CO2 terpolymers are proved to be gradient structure and show two separated T g s. To synthesize polycarbonate-type triblock copolymers, a tandem strategy is employed to copolymerize CHO/CO2 for preparing poly(cyclohexene carbonate) (PCHC) as di-functional macroinitiator first, and then trigger the EO/CO2 copolymerization to afford poly(ethylene carbonate) (PEC) as two external blocks. A series of high-molecular-weight PEC-PCHC-PEC triblock copolymers are obtained with phase separation microstructures ( M n = 126–275 kg mol −1 ). All obtained copolymers are characterized by 1 H NMR, diffusion-ordered spectroscopy (DOSY), gel permeation chromatography (GPC), and differential scanning calorimetry (DSC). Thermogravimetric analysis (TG) and mechanical test show that the obtained terpolymers exhibit superior and tailorable performances compared with PEC. Graphical Abstract: Random, gradient and triblock copolymers are synthesized via metal-free catalyst with the purpose of improving the performances of poly(ethylene carbonate). ga1 Highlights: Synthesis of high-molecular-weight EO/CO2 -based copolymers catalyzed by metal-free catalyst at the first time. The mechanical and thermal performances of EO/CO2 copolymer were improved by the introduction of rigid CHO or PA. PCHC-PEC-PCHC triblock copolymers were synthesized via tandem strategy.